Buried Waste in the Seabed - Acoustic Imaging and Bio-toxicity Results from the European SITAR Project - Blondel, Philippe; Caiti, Andrea (Geophysical Sciences, 2007)
Buried waste on the seabed is a major source of pollution. But, very often, waste sites are not known until a serious problem occurs, or are not adequately mapped. Recent examples around Europe include WWI and WWII ammunition dump sites (e.g. Beufort Dyke in the UK), dumped nuclear submarines in the Arctic Seas, clandestine or hidden toxic-waste in the Baltic Sea and the North Sea.. Even if properly documented, waste sites evolve with time (dumped material can move with currents and tides, especially on a scale of decades; toxic-material barrels can corrode and leak). This book shows the results of a concerted EU-funded effort to tackle this problem and find innovative ways to identify and map toxic waste sites ona the seabed, whether they have been covered with sediments or not. These results are applicable to any region on the seabed in the entire world.